Analisis PSAK 109 terhadap Pengakuan, Pengukuran, Penyajian, dan Pengungkapan Dana Non Halal Periode Januari-Desember 2017 (Studi Kasus pada LAZ Dompet Amanah Umat Sidoarjo) - Choir, Uswatul (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2019)
This journal is the result of qualitative research that aims to answer questions about how the implementation of recognition, measurement, presentation, and disclosure of the Dompet Amanah Umat LAZ Non-Halal LAZO fund and its analysis. The research method used is qualitative with the type of case study research. Data collection through interviews with the finance department and secretary of LAZ Dompet Amanah Umat Sidoarjo and documentation, data analysis techniques used in this study are from the results of interviews and documentation, then the data that has been obtained is processed and analyzed after it has been concluded and interpreted. The results of the study indicate that amil has acknowledged the addition of funds obtained from conventional bank interest as non- expensive funds according to the amount received. Amil has also provided non-halal funds that have been separated from zakat, infaq, and alms funds. However, the journaling and disclosure at the LAZ Dompet Amanah Umat is not in accordance with PSAK 109. Amil has not been able to raise the existence of non-halal funds at the time of disclosure